Penerapan Strategi Self Management Melalui Bimbingan Kelompok untuk Mengurangi Kecanduan Media Sosial Pada Siswa di MAN 4 Agam - Meta Rofiana; Linda Yarni; Alfi Rahmi; Hidayani Syam (Departement of Mathematics Education, 2023)
The background of this research is that the majority of students who have social media experience addiction to social media as in class they steal situations to open cellphones to open social media (Instagram, Facebook and WhatsApp). This study aims to determine the effect of applying self-management techniques through group guidance to overcome social media addiction in class XI MAN 4 Religion students in the 2021/2022 academic year. This study uses quantitative research with the type of research is experimental (pre-experimental designs one-group pretest-posttest design). The population in this study were 110 students of class XI MAN 4 Agam. Using a purposive sampling technique, a sample of 16 students who experienced high social media addiction was obtained. The data collection technique in this study used a social media addiction questionnaire with a closed questionnaire as well as data processing techniques and data analysis techniques using Microsoft Excel and SPSS 22.0 for Windows. Based on the data analysis, it shows that the value of rcount is 0.472 > rtable is 0.468, and by using a significance limit of 0.05. From the results of the study it also appears that with the application of self-management strategies 31.25% of students have low social media addiction and 68.75% of students have moderate social media addiction. So it can be concluded that there is a significant influence between self-management strategies through group guidance on social media addiction in students at MAN 4 Agam. Which means Ha is accepted and Ho is rejected. Based on the results of the coefficient of determination obtained results of 98.5%. Based on this value, it can be interpreted that the effect of implementing self-management strategies on reducing social media addiction in students is 98.5%, while 1.5% is influenced by other factors not included in this study.